New anti-corrosion pigment based on natural aluminosilicate with a layered structure - Danyliak, M.-O.M.; Korniy, S.A. (Problems of Tribology, 2026)
According to scanning electron microscopy results the montmorillonite particles are in the form of curved plates that tend to agglomerate. Using EDX analysis, it was established that the initial montmorillonite was Ca, Mg – form of montmorillonite. Due to the mechanochemical modification of montmorillonite, intercalation of Zn2+ cations into the layered structure of natural montmorillonite occurred, and phosphate anions were able to form surface adsorption complexes with positively charged edge surfaces of montmorillonite through the acidic environment of the crystal hydrate of the salt Zn(H2PO4)2·2H2O, while the content of zinc and phosphorus is ~5 wt. % and ~ 4 wt. %, respectively. It was established that the obtained pigment based on mechanochemically modified montmorillonite increases the corrosion resistance of the aluminium alloy in an acid rain environment with pH = 4.5 by potentiodynamic polarization and electrochemical impedance spectroscopy methods. The inhibitory effect of mechanochemically modified montmorillonite consists in the release of Zn2+ cations from montmorillonite containers, which, interacting with OH– anions, form zinc hydroxides at the cathode sites, and the slowing down of electrochemical corrosion occurs due to the formation of phosphates at the anode sites of the aluminium alloy. It was established that the protection degree of the aluminium alloy in the acid rain environment with mechanochemically modified montmorillonite was above 90 %. Thus, montmorillonite, an aluminosilicate mineral of natural origin, is a promising material for obtaining new eco-friendly anti-corrosion pigments in paint and varnish coatings to ensure long-term protection of metal products